Artificial agri‐environment scheme ponds do not replicate natural environments despite higher aquatic and terrestrial invertebrate richness and abundance. Issue 2 (13th September 2020) - Reyne, Marina; Nolan, Myles; McGuiggan, Henry; Aubry, Aurélie; Emmerson, Mark; Marnell, Ferdia; Reid, Neil
Abstract: Farmland ponds are a highly threatened freshwater habitat which has undergone dramatic losses during the last 200 years due to land drainage schemes and agricultural intensification. Agri‐environment schemes (AES) incentivize farmers to adopt farming methods to benefit biodiversity, yet there are a paucity of data evaluating the success of artificially created AES ponds as analogues of natural ponds in an attempt to recreate lost environments. We examined variation in environmental parameters and aquatic and terrestrial invertebrate communities between 38 natural ponds and 91 artificial ponds that were created in south‐west Ireland ( n  = 129). Artificial ponds in agricultural grassland did not replicate natural ponds in adjacent semi‐natural habitats differing significantly in size, pH, conductivity, productivity (indicated by submerged and emergent plant cover including algae) and surrounding vegetation structure that is, sward height. These differences significantly influenced aquatic and terrestrial invertebrate community structure with a suite of indicator taxa in both natural and artificial ponds. The conservation value of artificial ponds in agricultural grasslands should not be underestimated as they had 43% higher aquatic species richness and 33% higher aquatic species abundance than natural ponds in adjacent semi‐natural habitats. Synthesis and applications . We demonstrate that artificial agri‐environment scheme ponds created in agricultural grasslands, whilst not direct analogues of natural ponds in adjacent semi‐natural habitats, do fulfil a role in preserving high local biodiversity albeit representing a different community of species. Creation of ponds in farmland as well as in adjacent natural habitats could provide a wider range of environmental conditions and richer associated macroinvertebrate communities, increasing landscape connectivity and further enhancing regional biodiversity. Abstract : We demonstrate that artificial agri‐environment scheme ponds created in agricultural grasslands, whilst not direct analogues of natural ponds in adjacent semi‐natural habitats, do fulfil a role in preserving high local biodiversity albeit representing a different community of species. Creation of ponds in farmland as well as in adjacent natural habitats could provide a wider range of environmental conditions and richer associated macroinvertebrate communities, increasing landscape connectivity and further enhancing regional biodiversity.